Ultrasound effects on invertase from Aspergillus niger - Vargas, LHM; Piao, ACS; Domingos, R. N.; Carmona, E. C. (Kluwer Academic Publ, 2004)
Ultrasound effects on the release and activity of invertase from Aspergillus niger cultivated in a medium containing sucrose and peptone and in another with sugar-cane molasses and peptone were investigated. Irradiation was conducted for periods of 2 - 10 min. with waves of amplitude 20 and 40 using an ultrasound processor of 20 kHz. Product formation was determined as reducing equivalents formed by time units using 3,5-dinitrosalicylic acid. Total and specific activities of the culture supernatants were compared in the presence and absence of sonication. Both amplitudes promoted a significant increase of total invertase activity in the time periods investigated and the highest values were obtained with an amplitude of 20. Ultrasound irradiation caused cell disruption, thus releasing invertase and, after 4 min, activation of the enzyme also occurred. The best conditions for production, extraction and activation of invertase were in molasses medium containing peptone and irradiation with ultrasound waves at 20 for 8 min. This method showed high efficiency for the extraction and activation of invertase from A. niger as well as a great potential for use in industrial processes.
Keywords: Aspergillus niger; enzyme release; invertase; sugar-cane molasses; ultrasound